2007
DOI: 10.1016/j.bmcl.2006.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular iodine catalyzed synthesis of aryl-14H-dibenzo[a, j]xanthenes under solvent-free condition

Abstract: Molecular iodine efficiently catalyzes the reaction of beta-naphthol and araldehydes on a preheated hot plate at 90-95 degrees C to give biologically active aryl-14H-dibenzo[a, j]xanthenes under solvent-free condition. The yields are excellent and the reactions go to completion within 15-20 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…Different catalysts such as sulfamic acid [10], p-TSA [11], selectfluor TM [12], iodine [13], silica sulfuric acid [14], Yb(OTf) 3 [15] and ionic liquids [16] find application in the synthesis of benzo [a]xanthenes. The existing methods have not been conceded for the synthesis of tetrahydrobenzo [c]xanthene-11-ones from a-naphthol (Scheme 1), this is because, the electron density at the b-position of the a-naphthol is not sufficient for the formation of the corresponding ortho-Quinone Methides (o-QMs, Scheme 2) under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Different catalysts such as sulfamic acid [10], p-TSA [11], selectfluor TM [12], iodine [13], silica sulfuric acid [14], Yb(OTf) 3 [15] and ionic liquids [16] find application in the synthesis of benzo [a]xanthenes. The existing methods have not been conceded for the synthesis of tetrahydrobenzo [c]xanthene-11-ones from a-naphthol (Scheme 1), this is because, the electron density at the b-position of the a-naphthol is not sufficient for the formation of the corresponding ortho-Quinone Methides (o-QMs, Scheme 2) under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SiO 2 -NaHSO 4 has been used in the protection of aldehydes with 2-mercaptoethanol [18]. In a continuation of our work into the synthesis of biologically active heterocyclic compounds using readily available, inexpensive, and environment friendly catalysts [21][22][23][24][25][26], herein we are report the synthesis of octahydro-quinazolin-2,5-diones by the one-pot multi-component reaction of aromatic aldehydes, dimedone, and urea using SiO 2 -NaHSO 4 as an efficient catalyst in water. We have found that SiO 2 -NaHSO 4 catalyzes the reaction between aromatic aldehydes, dimedone, and urea in an aqueous medium efficiently to afford the desired products in excellent yield within 1-2 h. The catalyst can be easily prepared [18] and safely handled, making the method more advantageous over other conventional methods and catalysts.…”
Section: Catalytic Performance Of Sio 2 -Nahsomentioning
confidence: 99%
“…Richards and Loomis were the first to report the use of ultrasound in organic syntheses in the year 1927 [22]. In continuation of the work from our laboratory to develop new methods for the synthesis of various biologically important molecules such as N,N-disubstituted ureas/thioureas [23], azines [24], b-acetamido-b-arylpropiophenones [25] and aryl-14H-dibenzo[a,j]xanthenes [26], we are reporting an effective protocol for the synthesis of 4,6-diarylpyrimidin-2(1H)-ones using atomized sodium in THF via a one-pot three-component cyclocondensation of methyl ketones and urea with various substituted aryl aldehydes under ultrasonic condition. This one-pot route is mild, energy efficient, and inexpensive.…”
Section: Introductionmentioning
confidence: 99%